With seaplane and sledge in the Arctic - Binney, George (Hutchinson, 1925)
Narrative of Oxford University Arctic Expedition to Nordaustlander, Spitsbergen, 1924; experiment in use of seaplane in research; topographic, geological, meteorological, biological and geographical studies; first crossing of Nordaustlander.
Keywords: Oxford university Arctic expedition, 1924; Arctic regions